WANPRESTASI PENGUSAHA PT. AGRO MANDIRI LAMPUNG DALAM PERJANJIAN JUAL BELI BIJI BUAH KOPI ROBUSTA TERHADAP CV.LANGKAH BARU DI DESA PAMAH SALAK KECAMATAN JARAI KABUPATEN LAHAT SUMATERA SELATAN - EGA MAHARANI NIM. A1011191270 (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac In order to meet the needs of coffee powder production, PT. Agro Mandiri Lampung has entered into a sale and purchase agreement for Robusta coffee beans with CV. Langkah Baru. CV. Langkah Baru is one of the coffee bean producing companies in Lahat Regency. When the agreement is held, the parties make a written statement. This statement has the function of clarifying the rights and obligations of each party; besides, being legally binding and it can be proven in the event of a dispute or default between the two parties. At the beginning of the implementation of the sale and purchase agreement for Robusta coffee beans between PT. Agro Mandiri Lampung with CV. Langkah Baru went well and smoothly, however, as time went on in the agreement, PT. Agro Mandiri Lampung was unable to pay the price of the Robusta coffee beans as agreedThe formulation of the problem is